Construction of hole-transported MoO₃₋ₓ coupled with CdS nanospheres for boosting photocatalytic performance via oxygen-defects-mediated Z-scheme charge transfer - Wu, Yan (2021)
The establishment of Z-scheme charge transfer between semiconductors is an effective method to improve the performance of hybridized semiconductor photocatalysts. Herein, the novel photocatalysts consisting of MoO₃₋ₓ and varying amounts of cadmium sulfide (CdS) nanospheres were successfully prepared via the one-pot hydrothermal method in the presence of polyvinylpyrrolidone (PVP). It is indicated that the PVP not only served as the reducing agent for the formation of oxygen defects in MoO₃₋ₓ, but also the cross-linking agent for the coupling between MoO₃₋ₓ and CdS. The CdS/MoO₃₋ₓ composite allowed for higher visible-light photocatalytic performance for enhanced removal of methylene blue and tetracycline with an efficiency of 97.6% and 85.5%, respectively. The improved performance of the CdS/MoO₃₋ₓ composite was found to be mainly attributable to the remarkable charge carrier separation and transfer between CdS and MoO₃₋ₓ based on the favorable hole-transporting nature and oxygen deficiencies of MoO₃₋ₓ. In addition, the hole-oxidized photocorrosion of CdS was efficiently suppressed due to the presence of hole-attractive MoO₃₋ₓ. At the solid interface, an oxygen-defects-mediated Z-scheme charge carrier transfer pathway was proposed as the underlying mechanism for the superior photocatalytic reaction.